An act of terror and an act of hate: national elite and populace newspaper framing of pulse nightclub shooting - Valcore, Jace L. (Criminal justice studies, 2020)
The Pulse nightclub mass shooting is a defining event for the LGBTQ and Latinx communities. It signified that much remains to be done to achieve true equality and equitable treatment over and above the symbolic mentions of it in law and public policy. The news media is an important mechanism for communication of meaning following tragic and painful events such as the Pulse shooting. This study examined how the Pulse nightclub shooting that occurred on 12 June 2016, was covered by influential national newspapers in the United States, The New York Times, The Washington Post, and USA Today, to determine how the event was framed, what types of sources were relied upon, and what types of social and legal solutions were emphasized. The unit of analysis was direct and indirect quotes in each news article. Content analysis revealed that the dominant framing of the attack was that of a terrorist act committed by a pathological, ideologically motivated offender. The most common control mechanism discussed were soft measures, particularly gun control. Little attention was given to the victims or the anti-LGBTQ nature of the shooting.